Integrating VR in Communication Practices: A Multisectoral Narrative Review with Emphasis on Education, Healthcare, and Marketing in Global Contexts - Pratama, Alfian; Patrissia, Ressa Uli (Communica : Journal of Communication, 2024)
The integration of Virtual Reality (VR) and immersive technologies in communication is reshaping how individuals engage, interact, and learn across various sectors. This narrative review explores the applications and challenges of VR in education, healthcare, marketing, and cultural heritage communication. The study aimed to analyze current literature to uncover the transformative potential and limitations of VR-based communication practices. The review utilized a comprehensive literature search in databases such as Scopus, PubMed, and Google Scholar using keywords including "Virtual Reality," "Immersive Communication," "Augmented Reality," and "Narrative Review." Inclusion criteria prioritized peer-reviewed studies from 2010 to 2024 focusing on VR applications in communication contexts. Studies unrelated to communication, non-empirical works, and unpublished materials were excluded. Results show that VR enhances learning outcomes, social-emotional skills, and engagement in educational settings; improves therapeutic communication and patient care in healthcare; strengthens brand engagement in marketing; and facilitates access to cultural content globally. However, key challenges remain, including infrastructure limitations, cost barriers, social adaptation, and regulatory issues. Factors such as policy support, stakeholder training, and equitable design are vital for broader adoption. This review emphasizes the strategic role of VR in modern communication while calling for interdisciplinary research and policy reforms to ensure ethical and inclusive deployment. Addressing these systemic and contextual barriers is essential to realizing VR’s full potential.